A frequency-agile Na lidar for the measurement of temperature and velocity in the mesopause region - White, Michael Alton, author; Krueger, David A., advisor; She, Chiao-Yao, advisor (Colorado State University. Libraries, 1999)
A clear understanding of the energetics and dynamics of the Earth's mesopause region, located between 80 and 110km. has been pursued for years by the atmospheric modeling and global change communities. These theoretical efforts, however, require long-timespan data sets including both temperature and velocity in the mesopause region. Modification of Colorado State University's existing two-frequency Na-fluorescence temperature lidar to measure accurate line-of-sight velocity has been accomplished, incorporating several improvements to the original system. To measure velocity from Doppler-shifting, as well as temperature from Doppler-broadening, at least three operating frequencies of the lidar transmitter are required. However, the time necessary to cycle between output frequencies in the two-frequency temperature lidar is long enough to allow error from atmospheric change between integrating periods to be non-negligible, complicating the addition of another frequency by the same tuning method. A new method, therefore, by which the lidar output frequency may be changed on a shot-to-shot basis has been developed using a unique tandem acousto-optic modulator system, allowing simultaneous integration of the three operating frequencies. Vertical velocities derived from routine operation of the 3-frequency lidar suggest the presence of a systematic frequency shift in the pulsed output of the lidar. Therefore, a frequency monitoring system utilizing a fortuitously located iodine absorption line has been developed whereby the frequency lineshape-centers of the lidar output puses are measured and any shift accounted for in the temperature/velocity calculation. With several nights of frequency-monitored lidar temperature and vertical wind data, greatly improved accuracy is observed, allowing for the use of this lidar for detailed energetics and wind field measurements.
Keywords: optics; atmosphere; remote sensing